P431 Teduglutide use and nutritional outcomes in short bowel syndrome with intestinal failure: a real-world claims database analysis. (27th May 2021) - Micic, D; Jiang, J; Chen, L; Fan, T; Mu, F; Satija, A; Downes, N; Shrestha, S; Wu, E; Swallow, E; Wojtowicz, A; Raphael, B P
Abstract: Background: Teduglutide (TED) is a glucagon-like peptide 2 analogue approved for the treatment of patients with short bowel syndrome (SBS) requiring parenteral support (PS). SBS is a rare condition resulting from a reduced absorptive surface area of the small intestine, most commonly due to inflammatory bowel disease (IBD). Patients with SBS with intestinal failure (SBS-IF) remain dependent on PS to maintain adequate calorie, fluid, electrolyte and micronutrient stability. In phase 3 clinical trials, TED reduced PS requirements in patients with SBS-IF. This study aimed to assess PS use and discontinuation rates among patients with SBS on TED using real-world data. Methods: This retrospective cohort study of adults with SBS-IF (≥18 years) with ≥1 TED pharmacy claim(s) used the US-based administrative healthcare claims IBM MarketScan database (2009–2019). The first TED claim was defined as the index date. Patients required ≥6 months of continuous enrolment prior to index date (baseline period) and no history of malignancy. Primary analysis was conducted during the follow-up period (index date to earliest of continuous enrolment end or 2 years post-index). A sensitivity analysis was also conducted among the cohort during the TED utilization period (index date to the earliest of continuous enrolment end or TED discontinuation). Patients required PS use during both baseline and follow-up/TED utilization periods (primary and sensitivity analyses). PS discontinuation was defined as a PS utilization gap of ≥30 days. A generalized estimating equation linear regression model evaluated if PS use (days/week) changed significantly from baseline to selected time points post-index. Results: Of 110 identified patients with SBS-IF, mean age was 53.4 (SD 13.2) years and 77 (70%) were women. Included were 51 (46%) patients with Crohn's disease and 20 (18%) with ulcerative colitis. The main comorbidities were renal disease (23%) and liver disease (15%). PS frequency was 4.6 (2.5), 3.3 (2.9), 2.9 (3.0) and 3.6 (3.0) days/week at baseline and months 6 ( p <0.0001), 12 ( p <0.0001), and 24 ( p =0.0267), respectively. PS discontinuation increased over time to 34.4%, 46.7% and 65.2% at 3, 6, and 12 months, respectively. The sensitivity analysis demonstrated similar rates of PS use and discontinuation. Conclusion: In this real-world study of adults with SBS-IF, including >50% with IBD, TED was associated with PS reductions comparable to those achieved in clinical trials and higher PS discontinuation rates even when using a conservative analysis approach. Future research will be required to determine individual predictive factors of PS discontinuation.